EDUCATION, HEALTH AND ECONOMIC GROWTH IN AFRICAN COUNTRIES - EGGOH, COMLANVI JUDE; SOSSOU, Gilles (My University, 2015)
This paper provides new empirical evidence concerning the relationship between human capital (measured by education and health related variables) and economic growth for a large sample of 49 African countries over the period from 1996 to 2010. Using traditional cross-section and dynamic panel techniques, we find that public expenditures on education and health have a negative impact on economic growth, whereas human capital stock indicators have a slight positive effect. Furthermore, our empirical investigations suggest that education and health spending are complementary. Then, public investment in education and health should be jointly increased and their efficiency in order to expect positive impact of human capital on growth in African countries.
Keywords: Human Capital; Education; Health; Economic Growth; Panel Data; Africa